2022
DOI: 10.3389/fpsyg.2022.969918
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with a high level of unmet needs and their prevalence in the breast cancer survivors 1–5 years after post local treatment and (neo)adjuvant chemotherapy during the COVID-19: A cross-sectional study

Abstract: ObjectiveTo assess the prevalence of unmet needs in post-treatment breast cancer survivors and identify sociodemographic, clinical, and psychosocial variables associated with reported unmet needs during the COVID-19 pandemic.Materials and methodsIn this cross-sectional study, 430 post-treatment breast cancer survivors, ranging between 1 and 5 years after the procedure, completed the Cancer Survivors’ Unmet Needs (CaSUN) questionnaire from September 2021 and January 2022. The multivariate logistic analysis iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Unmet supportive care needs were common for all BC patients throughout the pandemic, including physical and psychological needs, communication with clinicians, health system information needs, and other financial and social needs [ 30 ]. A previous quantitative study conducted during the pandemic found that unmet needs for BC survivors can be addressed with either comprehensive care or psychological and emotional support and women who reported more unmet needs also reported a significantly lower quality of life [ 15 ]. The results of our study found that women of low SES experienced greater disruption to routine care and increased financial difficulties specific to BC, which is consistent with research conducted prior to the pandemic [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmet supportive care needs were common for all BC patients throughout the pandemic, including physical and psychological needs, communication with clinicians, health system information needs, and other financial and social needs [ 30 ]. A previous quantitative study conducted during the pandemic found that unmet needs for BC survivors can be addressed with either comprehensive care or psychological and emotional support and women who reported more unmet needs also reported a significantly lower quality of life [ 15 ]. The results of our study found that women of low SES experienced greater disruption to routine care and increased financial difficulties specific to BC, which is consistent with research conducted prior to the pandemic [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A failure to address unmet needs can have a negative impact on an individual’s quality of life and other health outcomes [ 14 ]. Previous research conducted during the pandemic identified unmet needs for individuals living with a diagnosis of BC such as psychological and emotional support, management of side effects, complementary therapy, communication among healthcare providers, local health care services, and transportation [ 15 ]. However, similar research has not been conducted qualitatively post-pandemic to identify lasting unmet needs.…”
Section: Introductionmentioning
confidence: 99%
“…All eligible female BC survivors attending hospital followup appointments during this period were invited to participate. The detailed inclusion and exclusion criteria for this cross-sectional study have already been described in another publication ( 22 ). Prior to participation, all individuals were informed about the purpose of the study and gave informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we collected socio-demographic, clinical and patient-reported data. Comprehensive descriptions of these measures with validation reports can be found in the original study ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation